2014
DOI: 10.1007/s00381-014-2378-7
|View full text |Cite
|
Sign up to set email alerts
|

The inferior petrosal sinus: a comprehensive review with emphasis on clinical implications

Abstract: Knowledge of the inferior petrosal sinus is of great importance for open surgical approaches to the skull base and endovascular access to the cavernous sinus and sellar region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“… 12) The IPS is the main posterior drainage pathway of the CS and is situated in the cranial surface of the petroclival fissure. 1 , 60) The IPS also receives venous drainage from the labyrinth through the vein of the cochlear aqueduct, 8) brainstem and inferior cerebellar surface through bridging veins from the pial venous system of the pons or the medulla oblongata. 28 , 29) Padget 5) described the IPS development as a medial derivative of the pro-otic sinus accompanying the growth of the skull base chondrocranium.…”
Section: Discussionmentioning
confidence: 99%
“… 12) The IPS is the main posterior drainage pathway of the CS and is situated in the cranial surface of the petroclival fissure. 1 , 60) The IPS also receives venous drainage from the labyrinth through the vein of the cochlear aqueduct, 8) brainstem and inferior cerebellar surface through bridging veins from the pial venous system of the pons or the medulla oblongata. 28 , 29) Padget 5) described the IPS development as a medial derivative of the pro-otic sinus accompanying the growth of the skull base chondrocranium.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our experience, the probing guidewire tip could easily lodge in the anastomotic channels of the basilar venous plexus, which course in a direction similar to that of the IPS. 12 Therefore, the guidewire tip should be turned upward to adapt to the course of IPS at its upper curve (Fig 2) and to avoid entering the anastomotic channels. Accordingly, we found that the passage of the upper curve with the probing guidewire is associated with a higher technical success rate of reaching the CS with the microcatheter.…”
Section: Discussionmentioning
confidence: 99%
“…2) The internal auditory vein also participates in the venous drainage of the inner ear via the internal auditory meatus. It empties into the IPS, 3) the SPS or the transverse sinus, 4) or the great anterior cerebellar vein. 2) The tympanic cavity can be drained by several veins accompanying the tympanic arteries and the branches of the facial or the glossopharyngeal nerve through the bony canals or apparatuses of the petrosal bone into the pterygoid plexus, the retromandibular vein, or the middle meningeal vein, such as the superior tympanic vein passing through the lessor petrosal canaliculus or the inferior tympanic vein passing through the tympanic canaliculus.…”
Section: Discussionmentioning
confidence: 99%